Interaction of the Capsular Polysaccharide A from Bacteroides fragilis with DC-SIGN on Human Dendritic Cells is Necessary for Its Processing and Presentation to T Cells - Bloem, Karien; Garcia-Vallejo, Juan J.; Vuist, Ilona M.; Cobb, Brian; van Vliet, Sandra J.; Van Kooyk, Yvette (Frontiers in Immunology, 2013)
The zwitterionic capsular polysaccharide A (PSA) of Bacteroides fragilis is the first carbohydrate antigen described to be presented in major histocompatibility complex (MHC) class II for the induction of CD4+ T cell responses. However, the identity of the receptor mediating binding and internalization of PSA in antigen presenting cells remains elusive. C-type lectins are glycan-binding receptors known for their capacity to target ligands for antigen presentation to T cells. Here, we investigated whether C-type lectins were involved in the internalization of PSA and identified dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) as the main receptor for PSA on human dendritic cells (DC). The induction of PSA-specific T cell proliferation appeared to be completely dependent on DC-SIGN. These data reveal a crucial role for DC-SIGN in the endocytosis and routing of PSA in human DC for the efficient stimulation of PSA-specific CD4+ T cells.